EFFECT OF SUSTAINABILITY REPORT ON MANUFACTURING SECTOR FIRM VALUE WITH PROFITABILITY AS A MODERATION VARIABLE - Dian Kurniawati; Esti Riwayati, Hedwigis; Akhmad Firdaus (Dinasti Publisher, 2022)
This study aimed to obtain empirical evidence of the effect of sustainability report disclosure on firm value and the effect of sustainability report on firm value with profitability as a moderating variable. This study investigates the relevance of sustainability report disclosure in manufacturing sector companies listed on the Indonesia Stock Exchange for the period 2016-2020. Data were collected from 11 manufacturing sector companies that met the predetermined sample criteria. The results of this study empirically prove that sustainability report disclosure affect firm value and profitability strengthening the positive effect of the sustainability report on firm value.